Resolvemos problemas de multiplicación de un número por otro de dos cifras - Zumaeta Arista, Romel Wilson (2016)
In the present instructional design of a class at the classroom level, different strategies were _x000D_ developed and applied during the development of the learning activity called: we solve _x000D_ multiplication problems of a number by another of two figures. This work was proposed to _x000D_ students of the third grade of primary education in the area of mathematics._x000D_ The application of the learning experience was based on the approach focused on _x000D_ problem solving. During the process, we worked with the problem solving methods, the _x000D_ analytical - synthetic and the inductive - deductive._x000D_ To start the activity, a challenge or cognitive conflict was proposed to arouse the _x000D_ interest of the students and, for the understanding of the session, we worked with didactic _x000D_ processes in the mathematics learning session. The processes are the following: _x000D_ understanding of the problem, search for strategies, representation, formalization, reflection _x000D_ and transfer. Likewise, in the execution, the techniques of the exhibition, the question, the _x000D_ individual and collective work were considered. The evaluation was carried out using the _x000D_ hetero-evaluation technique, which was consolidated in a checklist. At the end of the _x000D_ learning activity, it was possible to verify that the students achieved the learning proposed _x000D_ in the learning session.